2020
DOI: 10.2174/1389450121666200422084414
|View full text |Cite
|
Sign up to set email alerts
|

The Association and Influencing Factors between Antipsychotics Exposure and the Risk of VTE and PE: A Systematic Review and Meta-analysis

Abstract: Background: Different clinical studies have given inconsistent results on whether the use of antipsychotics increases the risk of thromboembolism. In this paper, we reviewed all relevant literature to provide suggestions for clinical diagnosis and treatment. Method: PubMed, Web of Science, EMBASE, MEDLINE, Cochrane and Scopus databases were thoroughly searched up to June 2019. Two researchers independently searched the literature, extracted data. Data were analyzed by Stata 12.0 software. Result: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The occlusion/occlusion-like syndrome conceptual background as a large multicausal class effect, peripheral and central was realized only quite recently [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Here, there was a general cytoprotective endothelial threat (i.e., a disturbed dopamine system as a long-lasting essential pitfall in cytoprotection maintenance [ 30 , 31 , 32 , 33 , 34 , 35 ], endothelium lesions, and thrombosis induced by neuroleptics [ 36 , 37 , 38 , 39 , 40 , 41 ], domperidone [ 42 ], and amphetamine [ 43 , 44 , 45 ]). This accorded a major challenge of multicausal pathology (i.e., major vessel occlusion [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] peripherally and centrally and similar noxious procedures [ 19 , 20 , 21 , 22 , 23 , 24 ] severely affecting endothelium function).…”
Section: Introductionmentioning
confidence: 99%
“…The occlusion/occlusion-like syndrome conceptual background as a large multicausal class effect, peripheral and central was realized only quite recently [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Here, there was a general cytoprotective endothelial threat (i.e., a disturbed dopamine system as a long-lasting essential pitfall in cytoprotection maintenance [ 30 , 31 , 32 , 33 , 34 , 35 ], endothelium lesions, and thrombosis induced by neuroleptics [ 36 , 37 , 38 , 39 , 40 , 41 ], domperidone [ 42 ], and amphetamine [ 43 , 44 , 45 ]). This accorded a major challenge of multicausal pathology (i.e., major vessel occlusion [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] peripherally and centrally and similar noxious procedures [ 19 , 20 , 21 , 22 , 23 , 24 ] severely affecting endothelium function).…”
Section: Introductionmentioning
confidence: 99%
“… 39 On the other hand, they are both risk factors for VTE and vascular injury. 40 , 41 Second, smoking should not be ignored though this study did not collect the smoking-relevant information from the participants. Previous studies have reported that schizophrenia patients have extremely high prevalence of smoking compared to the general population and patients with other psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those of previous reviews which found between 63.3% and 75% of patients were males [ 9 , 12 , 16 ]. In a meta-analysis that included a total of 31,514,226 subjects from 22 studies, Dai et al observed patients taking first- and second-generation antipsychotics [ 17 ]. These patients were at a higher risk of VTE than those who were not prescribed antipsychotics, and females taking antipsychotics had a higher risk of PE than males [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a meta-analysis that included a total of 31,514,226 subjects from 22 studies, Dai et al observed patients taking first- and second-generation antipsychotics [ 17 ]. These patients were at a higher risk of VTE than those who were not prescribed antipsychotics, and females taking antipsychotics had a higher risk of PE than males [ 17 ]. In the same study, the authors reported that clozapine users have significantly increased VTE risk [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation